2017
DOI: 10.1111/jar.12408
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in providing end‐of‐life care for people with intellectual disability: Health services access

Abstract: Improved access to end-of-life services is urgently required across both rural and metropolitan areas. Development of specialist training and support models for both disability and general healthcare staff may assist to reduce some identified barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…8,49,53,54,65,[71][72][73] In addition, several studies highlighted the need to educate registered nurses in both hospital and community settings in caring for patients with intellectual disabilities at the end of life. 8,44,61,[74][75][76] Inadequate training can heighten communication fears, 67 lead to lack of confidence among staff 51 and elevated levels of stress. 45 An intellectual disability support worker commented in a focus group discussion that there was a tendency of staff in hospital settings to put patients with intellectual disabilities and palliative care needs into the 'too-hard basket'.…”
Section: Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…8,49,53,54,65,[71][72][73] In addition, several studies highlighted the need to educate registered nurses in both hospital and community settings in caring for patients with intellectual disabilities at the end of life. 8,44,61,[74][75][76] Inadequate training can heighten communication fears, 67 lead to lack of confidence among staff 51 and elevated levels of stress. 45 An intellectual disability support worker commented in a focus group discussion that there was a tendency of staff in hospital settings to put patients with intellectual disabilities and palliative care needs into the 'too-hard basket'.…”
Section: Educationmentioning
confidence: 99%
“…45 An intellectual disability support worker commented in a focus group discussion that there was a tendency of staff in hospital settings to put patients with intellectual disabilities and palliative care needs into the 'too-hard basket'. 8 Contributing to this knowledge gap is the absence of formal protocols, policies and guidelines regarding endof-life care for people with intellectual disabilities. 45,55,62 A study examining guidelines in 11 European countries suggested that European national palliative care guidelines do not meet the needs of people with intellectual disabilities.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Transport is very difficult, particularly for those in rural areas who need to travel for employment and services [ 18 , 27 ], and is an additional barrier to accessing social supports [ 28 ]. Individuals and their carers in rural areas often have to wait long periods of time for services or travel considerable distances to access them [ 29 ]. This poor availability and associated delays can then compound medical problems, due to complications that have arisen as a result of postponement of treatment and support [ 30 , 31 , 32 ], which in turn can increase the burden on caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…(), McCallion et al. () and Wark, Hussain, Müller, Ryan, and Parmenter () documented a range of important problems with access to end‐of‐life health services.…”
Section: Policy Issuesmentioning
confidence: 99%